Horizontal Flow Grit Chamber Design - Bengtson, Harlan A. (McGraw-Hill's AccessEngineering., 2021)
This Excel workbook determines required tank dimensions (length, width and tank wall depth based on user input design values of average wastewater flowrate, horizontal velocity, tank freeboard, number of tanks in parallel, percentage additional length for inlet and outlet, and depth for grit storage). There is also a worksheet for design of an exit sutro weir to maintain the horizontal velocity in the tank at the design value.